2016
DOI: 10.1002/jgm.2930
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and non-toxic gene delivery by anionic lipoplexes based on polyprenyl ammonium salts and their effects on cell physiology

Abstract: The developed carriers constitute a group of promising lipofecting agents of a new type that can be utilized as effective lipofecting agents in vitro and they are also an encouraging basis for in vivo applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…Recently, PTAI were demonstrated by us to allow effective transfection of plasmid DNA complexes into cells [ 10 , 11 ]. The aim of this study was evaluation of PTAI as an efficient carrier of DNA vaccines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, PTAI were demonstrated by us to allow effective transfection of plasmid DNA complexes into cells [ 10 , 11 ]. The aim of this study was evaluation of PTAI as an efficient carrier of DNA vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…1 ). The PTAI were obtained as previously described [ 10 , 11 ], (patent PL 2012, B1 211824, Patent Office of the Republic of Poland). PTAI and helper lipids (DOPE, DC-cholesterol and DOPC were dissolved in 99.8% ethanol).…”
Section: Methodsmentioning
confidence: 99%
“…Among factors regulating the activity of transfection complexes, the size of the lipoplexes has been reported to be a major determinant of transfection efficiency [ 42 , 43 , 44 ]. The morphology and size of the lipoplexes formed by 1,4-DHP amphiphiles C12-Man-Q and D19 were analysed by the transmission electron microscopy (TEM) technique.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies we have shown that cationic polyisoprenoids are effective components of lipofecting mixtures (Rak et al 2016) and DNA vaccines vehicles (Stachyra et al 2017). In the present study, we have tested PTAI-6-8 and PTAI-10-14 in mixtures with helper lipids in the in vitro model of XC rat Rous sarcoma cell line before using these formulations in vivo in rats.…”
Section: In Vitromentioning
confidence: 92%
“…They are involved in cell response to environmental stress, glycosylation, and prenylation of proteins, and also they intensify the fusion and increase the permeability of model membranes (Swiezewska and Danikiewicz 2005). Recent studies (Gawrys et al 2014b(Gawrys et al , 2018Grecka et al 2016;Rak et al 2016;Stachyra et al 2017) show that cationic derivatives of polyisoprenoid alcohols, called PTAI, are non-toxic and may serve as lipofectants. In the present study, the effectiveness of two PTAI mixtures was investigated for plasmid DNA delivery into rats' cells and to rats and compared to the commercially available reagents for transfection: in vivo-jetPEI® (Polyplus-transfection) and Avalanche®-in vivo Transfection Reagent (EZ Biosystems LLC).…”
Section: Introductionmentioning
confidence: 99%